ANALISIS KELEMBAGAAN DAN FINANSIAL UNTUK PEMELIHARAAN DAN PERAWATAN RUSUNAWA BERDASARKAN SOFT SYSTEM METHODOLOGY - Putri Arumsari; Sofia W. Alisjahbana; Ayomi Dita Rarasati (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2022)
Social housing are houses intended for low-income society, and one of them is the public-rented flats. There are 2 (two) types of public-rented flats management model, the self-management model and the operational cooperation model. Public-rented flats in DKI Jakarta Province are mostly self-managed by the Management Unit of Public-Rend Flat (MUPRF) in the Department of Community Housing and Settlement (DCHS) of DKI Jakarta Province. However there are several issues in the MUPRF in managing the public-rented flats, such as rent arrears, deterioration of building quality and the budget availability for maintenance and treatment of public-rented flates. In the Indonesian Government, the Covid-19 pandemic has affected the National and Regional Budget, and one of them is the elimination of the maintenance and treatment budget of the public-rented flats in the Regional Budget of DKI Jakarta Province. Based on the soft system methodology method, it is identified that Technical Implementation Unit (TIU), National/Regional-Owned Enterprise (NOE/ROE), Public Service Agency/Local, Flats Resident Association (FRA), Housing Cooperatives and Housing Association as alternative organizational scheme, and Government, National/Regional-Owned Enterprise and Public-Private Partnership funding as alternatives for the financial scheme that can be implemented for the maintenance and treatment activity in the public-rented flats. Abstrak Rumah susun sewa (rusunawa) adalah perumahan yang diperuntukan untuk masyarakat berpenghasilan rendah. Terdapat dua skema organisasi pengelola rusunawa, yaitu swakelola dan kerja sama operasional. Rusunawa di Provinsi DKI Jakarta lebih banyak dikelola secara swakelola oleh Unit Pengelola Rumah Susun (UPRS) di Dinas Perumahan Rakyat dan Kawasan Permukiman (DPRKP) Provinsi DKI Jakarta. Namun terdapat beberapa permasalahan yang dialami oleh UPRS dalam pengelolaan bangunan rusunawa seperti adanya penunggakan serta penurunan kualitas bangunan gedung dan keterbatasan anggaran untuk kegiatan pemeliharaan dan perawatan bangunan gedung. Pandemi Covid-19 juga berdampak pada Anggaran Pendapatan dan Belanja Daerah Provinsi DKI Jakarta berupa pemotongan anggaran kegiatan pemeliharaan dan perawatan bangunan rusunawa. Berdasarkan soft system methodology, teridentifikasi Unit Pelaksana Teknik (UPT), Badan Usaha Milik Nasional/Daerah (BUMN/BUMD), Badan Layanan Umum/Daerah (BLU/BLUD), Perhimpunan Penghuni Rumah Susun (PPPSRS), koperasi dan Asosiasi Perumahan sebagai alternatif model kelembagaan dan pendanaan pemerintah, BUMN/BUMD dan Kerja sama pemerintah dengan badan usaha (KPBU) sebagai alternatif model finansial yang dapat diterapkan untuk kegiatan pemeliharaan dan perawatan bangunan rusunawa agar kegiatan tersebut terselenggara dengan optimum.